Progress and challenges in improving maternal health in the Tibet Autonomous Region, China - Labasangzhu; Bjertness E; McNeil EB; Deji; Guo Y; Songwathana P; Chongsuvivatwong V (Dove Medical Press, 2018)
Labasangzhu,1,2 E Bjertness,3 EB McNeil,2 Deji,1 Y Guo,4 P Songwathana,5 V Chongsuvivatwong2 1Department of Preventive Medicine, Tibet University Medical College, Lhasa, Tibet, China; 2Epidemiology Unit, Faculty of Medicine, Prince of Songkla University, Hatyai, Songkhla, Thailand; 3Department of Community Medicine and Global Health, Institute of Health and Society, University of Oslo, Oslo, Norway; 4Department of Health Policies and Management, School of Public Health, Peking University Health and Science Center, Beijing, China; 5Department of Adult and Elderly Nursing, Faculty of Nursing, Prince of Songkla University, Hatyai, Songkhla, Thailand Background: The maternal mortality ratio (MMR) of the Tibet Autonomous Region (hereinafter “Tibet”) is still five times higher than the national average. This study aims to identify the successes and pitfalls of the health system that might be related to the high mortality rate based on the WHO health system building blocks, focusing on human resources for health and health infrastructure and the impact on maternal health and outcomes. Methods: Sources of information include China’s central government and Tibet’s local government policies and regulations, health statistical yearbooks, maternal and child health routine reporting system, and English and Chinese online research articles. Joinpoint analysis was applied for MMR and maternal health service trends, and correlation test was used to test the relationship between maternal health services and outcomes. Results: Between 2000 and 2015, public health spending in Tibet increased 67-fold, the hospital delivery rate increased 70.1%, and the MMR dropped from 466.9 to 100.1 per 100,000 live births. However, the total number of health workers, qualified medical doctors, and registered nurses per 1,000 people were 4.4, 1.4, and 1.0, respectively, much lower than the national average (5.8, 1.8, and 2.4). In Tibet, there were 80 basic and 16 comprehensive emergency obstetric care (EOC) centers. On average, there were 12 basic and 2.5 comprehensive EOC centers per 500,000 of the population. Though it met the WHO’s recommendation, it might remain inadequate in the low population density of the area like Tibet. Conclusion: The shortage of health professionals and EOC centers and health information in predominantly remote rural areas with a scattered population still needs to be rectified. Keywords: health system, human resources for health, emergency obstetric care, Tibet